التأصيل للمصطلح والمفهوم النبوي "بيت المقدس": الحاجة لإعادة إحياء هذا المصطلح الإسلامي: Grounding the Concept of the Prophetic Terminology “Bayt al-Maqdis”: The Need for Reviving this Islamic Terminology - El-Awaisi, Abd al-Fattah (Journal of Al-Tamaddun, 2021)
Selecting the terminology is as important as creating concepts which represent the first nucleus and cornerstone in building perspectives from which the process of change emerges. On the other hand, the negligence of this pivotal and essential aspect leads to deficiencies and disastrous effects on community awareness and its preparatory process for change. Consequently, it is of utmost importance in the stage of knowledge-based preparation for the liberation of Bayt al-Maqdis (Islamicjerusalem) from the current occupation, to ground and root the concept and the prophetic terminology “Bayt Al-Maqdis”. As well as clarifying what is meant by this concept and term as a first foundational intellectual step for the upcoming liberation plan for this blessed and Holy Land. Thus, the key objective of this article is namely to ground the term and prophetic concept of “Bayt al-Maqdis,” and to clarify the need to revive this Islamic terminology. To achieve this goal, this article is divided into two parts; the first part discusses the origin of the name “al-Quds” and what is meant by it and its geographical boundaries in our current time, followed by discussing the origin of the term “Bayt al-Maqdis,” and how a new prophetic concept and term “Bayt al-Maqdis” was established with its sacred religious boundaries. The article presents the linguistic evidence from Arabic lexicons for the designation of the names “al-Quds” and “Bayt al-Maqdis,” the English translation of Bayt al-Maqdis to Islamicjerusalem and its consequences, and the importance of distinguishing between “Bayt al-Maqdis” and “al-Bayt al-Muqaddas” and identifying the meaning of the names associated with the Al-Aqsa Mosque and its compound. As for the second part of the article, it presents the urgent need for liberating the terminology and restoring its Islamic historical and geographical identity, thorough reviving the prophetic terminology used by the Messenger of God (PBUH), and clarifying the reasons that make the term “Bayt al-Maqdis” one of the best, most comprehensive, deepest, broadest and strongest terms. As well as the need for Muslims to use it and disseminate it. The discussion is then concluded by highlighting examples of the institutionalisation of the revival of the prophetic term “Bayt al-Maqdis” that has been commenced by the Academy of Islamicjerusalem Studies since 1990 worldwide.